Attractive Space Evaluation Method for HVDC Transmission Lines - György Kálecz; István Kiss; Bálint Németh (Energies)
High-voltage direct current (HVDC) transmission lines are increasing in number and overall length. This means their lightning protection must be of higher importance as well. Probability-modulated attractive space (PMAS) theory is a proven geometry-based method for lightning protection calculations. However, it cannot accurately assess the number and parameters of direct lightning strikes to the phase conductor of HVDC lines, because the effect of pole voltage on lightning attachment cannot be considered. This effect can be taken into account with leader progression models, which feature lightning physics models that can quantify the effect of the electric field around the phase conductor, which can be quite complex compared to geometric models in general. In this paper, a novel method, called the attractive space matrix, is presented to examine the effect of the DC electric field around the conductor on the attractive space. The algorithm is based on the physical background of the self-consistent leader inception and propagation model. The results could lead to improved lightning protection of HVDC lines and reduce the outages caused by direct lightning strikes.